# TO BOBPURSLEY

posted by .

def of average velocity = t^-1 (x - x0)

(average velocity = t^-1(x-x0))t=(avearge velocity)t + x0= x - x0 + x0 = x = (average velocity)t + x0

x = (average velocity)t + x0

def of average velocity were costant acceleration is assumed = 2^-1(v0 + v)

plug into

x = (average velocity)t + x0

x = 2^-1(v0 + v)t + x0

def of acceleration = t^-1(v-v0)

(a=t^-1(v-v0))t=(at=(v-v0))a^-1 = t = a^-1(v-v0)

t = a^-1(v-v0)

plug into x = 2^-1(v0 + v)t + x0

x = 2^-1(v0 + v)a^-1(v-v0) + x0

solve for v^2

x = 2^-1(v0 + v)a^-1(v-v0) + x0
simplfy
x = (a2)^-1(v^2 -v0^2)+ x0
OK so far
(x = (a2)^-1(v^2 -v0^2)+ x0)2a
(2a)x = (v^2-v0^2) + x0 the last term should be xo*2a ng
--------------------------------------

why i thought you had to subtract Xo from both sides???

• Physics -

def of average velocity = t^-1 (x - x0)

(average velocity = t^-1(x-x0))t=(avearge velocity)t + x0= x - x0 + x0 = x = (average velocity)t + x0

x = (average velocity)t + x0

def of average velocity were costant acceleration is assumed = 2^-1(v0 + v)

plug into

x = (average velocity)t + x0

x = 2^-1(v0 + v)t + x0

def of acceleration = t^-1(v-v0)

(a=t^-1(v-v0))t=(at=(v-v0))a^-1 = t = a^-1(v-v0)

t = a^-1(v-v0)

plug into x = 2^-1(v0 + v)t + x0

x = 2^-1(v0 + v)a^-1(v-v0) + x0

solve for v^2

x = 2^-1(v0 + v)a^-1(v-v0) + x0
simplfy
x = (a2)^-1(v^2 -v0^2)+ x0
OK so far
(x = (a2)^-1(v^2 -v0^2)+ x0)2a
(2a)x = (v^2-v0^2) + x0 the last term should be xo*2a ng
--------------------------------------

why i thought you had to subtract Xo from both sides???

## Similar Questions

1. ### HURRY........quick post

Simpson drives his car with an average velocity of 1.2 m/s to the north from the bust stop to the museum entrance. What is your displacement?
2. ### Physics

A boy is cycling at a constant speed along a straight road to his school. The postions of the boy after fixed time intervals are observed. a. What type of position-time graph can be expected for the motion of the bicycle?
3. ### AP Physics

I'm trying to derive the formula v^2 = v0^2 + 2a(x-x0) were zeros are subscripts my book tells me to derive it this way use the definition of average velocity to derive a formula for x use the formula for average velocity when constant …
4. ### Physics

def of average velocity = t^-1 (x - x0) (average velocity = t^-1(x-x0))t=(avearge velocity)t + x0= x - x0 + x0 = x = (average velocity)t + x0 x = (average velocity)t + x0 def of average velocity were costant acceleration is assumed …

I'm trying to derive the formula v^2 = v0^2 + 2a(x-x0) were zeros are subscripts my book tells me to derive it this way use the definition of average velocity to derive a formula for x use the formula for average velocity when constant …
6. ### physics

rewriting this, since it was typed wrong. In reaching her destination, a backpacker walks with an average velocity of 1.34 m/s, due west. This average velocity results because she hikes for 6.44 km with an average velocity of 2.68 …
7. ### physics

In this problem you will determine the average velocity of a moving object from the graph of its position as a function of time . A traveling object might move at different speeds and in different directions during an interval of time, …
8. ### Physics

Could someone please review my answers and tell me if I am on the right track?
9. ### physics..help PLZ!!

An object undergoes a displacement while being acted on by a constant force directed to the north. The work done on this object by the force is positive during the displacement. Which statement is necessarily true about the average …
10. ### Science Help Not sure

Within the Gaetz Lake Sanctuary in Red Deer, Alberta, is a looped trail that is 4 km long. Suppose a person walked all the way around the looped trail in 1 h, ending where he or she started. Which statement best describes this personâ€™s …

More Similar Questions